Exploring athletic trainers’ experience and perceptions associated with a multifaceted approach to concussion management - James Stavitz (Concussion)
Aim: To explore high school athletic trainers’ experience with, and perceptions of, a multifaceted approach to concussion management. Participants: A total of 20 high school athletic trainers that are certified and licensed to practice (if their state requires a license to practice) participated in this study. Materials & methods: A general qualitative design with descriptive coding and saturation was met at 20 interviews. Results: Lack of standardization allows assessment, referral and return-to-play experiences to vary significantly; referral experiences vary pending upon athletic trainers ability to refer to a trusted and responsive physician; barriers include clearances from unqualified physicians; pressure from coaches, parents and students to return students to play; benefits include increased knowledge and awareness resulting in more effective care for students. Conclusion: Athletic trainers have varying experiences and perceptions regarding their approaches to concussion management. However, there were many notable similarities in the experiences, pressures, barriers and benefits when applying their concussion protocol.